Synthesis and stability study of isocyano aryl boronate esters and their synthetic applications. Issue 36 (23rd March 2016) - Fang, Hao-Ping; Fu, Chia-Chieh; Tai, Chin-Kuen; Chang, Ken-Hao; Yang, Ru-Han; Wu, Meng-Ju; Chen, Hsien-Chi; Li, Chia-Jung; Huang, Shi-Qing; Lien, Wan-Hsiang; Chen, Chih-Hsin; Hsieh, Chung-Hung; et al.
Abstract : A facile synthesis of isocyano arylboronate esters is reported. Abstract : A facile synthesis of isocyano arylboronate esters is reported. Although tri-coordinate boron functional groups are commonly recognized as vulnerable to nucleophilic attack, the newly reported tri-coordinate isocyano arylboronate esters were found to be stable, albeit owing to the presence of an isocyano group. Theoretical calculations, using the DFT/B3LYP/6-31G(d, p) method, revealed that the electron delocalization between the aryl group and the boron atom might contribute to this stability. UV-vis spectroscopic investigations on 2-(4-isocyanophenyl)-4, 4, 5, 5-tetramethyl-1, 3, 2-dioxaborolane (2a ) were in agreement with the theoretical studies, showing a red-shifted absorption compared with that of phenylisonitrile. The reported strategy allows boronate ester substrates to survive throughout two-step operations. Two of the compounds synthesized were successfully exploited in Ugi and Passerini multicomponent reactions to afford corresponding products. In addition, two boron-containing tetrazoles were also prepared under environmentally benign conditions. These results demonstrated that functionalized isocyanides are stable and can be used as strategically as synthetic building blocks.